Assessment of the transfer, persistence, prevalence and recovery of DNA traces from clothing: An inter-laboratory study on worn upper garments. (September 2019) - Szkuta, Bianca; Ansell, Ricky; Boiso, Lina; Connolly, Edward; Kloosterman, Ate D.; Kokshoorn, Bas; McKenna, Louise G.; Steensma, Kristy; van Oorschot, Roland A.H.
Highlights: DNA transfer and recovery from upper garments was studied by four laboratories. DNA yield and DNA profile composition differed among laboratories and garment areas. Yield and profile composition was influenced by activities performed while wearing. The wearer of a garment is frequently, but not always, observed as a contributor. Co-habiting individuals are commonly observed in profiles from worn garments. Abstract: Among the various items recovered from crime scenes or persons involved in a crime event, clothing items are commonly encountered and submitted for forensic DNA sampling. Depending on the case circumstances and the activity-of-interest, sampling of the garment may concentrate on collecting DNA from the wearer, or from one or more offenders who have allegedly contacted the item and/or wearer. Relative to the targeted DNA, background DNA already residing on the item from previous contacts, or transferred during or after the crime event, may also be collected during sampling and observed in the resultant DNA profile. Given our limited understanding of how, and from where, background DNA is derived on clothing, research on the transfer, persistence, prevalence, and recovery (TPPR) of DNA traces from upper garments was conducted by four laboratories. Samples were collected from several areas of two garments, each worn on separate working or non-working days and individually owned by four individuals from each of the four laboratories, and processed from DNA extraction through to profiling. Questionnaires documented activities relating to the garment prior to and during wearing, and reference profiles were obtained from the wearer and their close associates identified in the questionnaire. Among the 448 profiles generated, variation in the DNA quantity, composition of the profiles, and inclusion/exclusion of the wearer and their close associates was observed among the collaborating laboratories, participants, garments worn on different occasions, and garment areas sampled.